Przemiany obyczajowe w Gubinie w pierwszej połowie wieku XIX - Kurowska, Hanna (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2011)
Guben in 1815 by the Treaty of Vienna was taken Saxony and became part of the Prussian state. This has contributed to changes in the law. Prussian “Landrecht” has become the determinant of some of the changes of behavior. Wedding ceremony took on a secular dimension to the legal regulations. Religious dimension has been lost, though, and so in the Protestant faith, the nature of marriage had the blessing and not a sacrament. Guben not so large as in previous centuries attended Sunday services, which complained to the clergy. Even baptism did not take place in the first days after birth, but the moment is shifted in time by several weeks. Very quickly and many residents have benefited from a reduction in the number of days on the advent and the post, thus changing the seasonality of marriages entered into a monthly – contains compounds readily bed previously overlooked such as December. But it seems that apart from marriage, a new form of coexistence between man and woman, concubinage. Evidenced by the significant proportion of illegitimate births and premarital conception.